2011
DOI: 10.1021/la200266e
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Microgel Magnetic/Optical Traps for SERS Ultradetection

Abstract: We report on the fabrication of a SERS substrate comprising magnetic and silver particles encapsulated within a poly(N-isopropylacrylamide) (pNIPAM) thermoresponsive microgel. This colloidal substrate has the ability to adsorb analytes from solution while it is expanded (low temperature) and reversibly generate hot spots upon collapse (high temperature or drying). Additionally, the magnetic functionality permits concentration of the composite particles into small spatial regions, which can be exploited to decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 43 publications
2
86
0
1
Order By: Relevance
“…Liz Marz á n et al reported that such optically active Au nanoparticles immobilized in responsive microgels, can be applied as molecular traps for surface-enhanced Raman scattering (SERS) [154,156] . The SERS performance of the gold particles can be signifi cantly improved by either increasing their size or by growing silver shells on Au cores as demonstrated in the case of Au@Ag@pNIPAM colloids with much higher SERS intensities than their Au@pNIPAM counterparts.…”
Section: Microgels/nanogels Network Composed Of Crosslinked Polymersmentioning
confidence: 99%
“…Liz Marz á n et al reported that such optically active Au nanoparticles immobilized in responsive microgels, can be applied as molecular traps for surface-enhanced Raman scattering (SERS) [154,156] . The SERS performance of the gold particles can be signifi cantly improved by either increasing their size or by growing silver shells on Au cores as demonstrated in the case of Au@Ag@pNIPAM colloids with much higher SERS intensities than their Au@pNIPAM counterparts.…”
Section: Microgels/nanogels Network Composed Of Crosslinked Polymersmentioning
confidence: 99%
“…The self-standing hydrogel-based substrate also shows good prospects with advantages of fast target gathering and easy to recycle from the matrix for detection [79]. Because of the fast mass transfer between the matrix and the hydrogel network, the hydrogel substrate can act as a scaffold for target capture and concentration [80]. Le et al prepared a gold NPs-embedded alginate gel for the detection of PAHs and found that the targets were captured by the three-dimensional network and brought close to the hot spots generated by the nanoparticles embedded in the gel, leading to significant SERS enhancement [80].…”
Section: Hydrogel-based Substrate For Target Gatheringmentioning
confidence: 99%
“…Because of the fast mass transfer between the matrix and the hydrogel network, the hydrogel substrate can act as a scaffold for target capture and concentration [80]. Le et al prepared a gold NPs-embedded alginate gel for the detection of PAHs and found that the targets were captured by the three-dimensional network and brought close to the hot spots generated by the nanoparticles embedded in the gel, leading to significant SERS enhancement [80]. Using this substrate, quantitative analysis of four PAHs such as benzo(a)pyrene was realized with LODs as low as to 0.365 nmol L −1 [81].…”
Section: Hydrogel-based Substrate For Target Gatheringmentioning
confidence: 99%
“…The adsorption of magnetic iron oxide NPs on the surface of pNIPAM microgel beads copolymerized with styrene in a core-shell fashion has been reported [28]. Even more complex structures have been realized by growing a pNIPAM corona on single Fe 2 O 3 covered with a sacrificial SiO 2 shell [29], or through the combination of magnetic and metallic NPs covered within the same pNIPAM microgel beads [30]. The later structure is illustrated in Figure 5, where a sketch describes the synthetic steps and the results are shown in the TEM images below.…”
Section: Pnipam Microgels and Nanoparticlesmentioning
confidence: 99%